Demystifying the concept of offsite manufacturing method: Towards a robust definition and classification system. Issue 2 (2nd December 2019) - Ayinla, Kudirat Olabisi; Cheung, Franco; Tawil, Abdel-Rahman
Abstract : Purpose: This study aims to develop a more inclusive working definition and a formalised classification system for offsite construction to enable common basis of evaluation and communication. Offsite manufacturing (OSM) is continuously getting recognised as a way to increase efficiency and boost productivity of the construction industry in many countries. However, the knowledge of OSM varies across different countries, construction practices and individual experts thus resulting into major misconceptions. The lack of consensus of what OSM is and what constitutes its methods creates a lot of misunderstanding across Architecture Engineering and Construction (AEC) industry professionals, therefore, inhibiting a global view and understanding for multicultural collaboration. Therefore, there is a need to revisit these issues with the aim to develop a deep understanding of the concepts and ascertain what is deemed inclusive or exclusive. Design/methodology/approach: A state-of-the-art review and analysis of literature on OSM was conducted to observe trends in OSM definitions and classifications. The paper identifies gaps in existing methods and proposes a future direction. Findings: Findings suggest that classifications are mostly aimed towards a particular purpose and existing classification system are not robust enough to cover all aspects. Therefore, there is need to extend these classification systems to be fit for various purposes. Originality/value: This paper contributes to the body of literature on offsite concepts, definition and classification, and provides knowledge on the broader context on the fundamentals of OSM.